The Tabernacle - Jurica Pavičić; Katarina Reljić; Antonija Primorac ([sic])
Bašić called him early that morning, just after seven.It was an autumn Saturday, lead-grey light seeped in through the shutters, and Niko was idling in bed, troubled by sleeplessness, observing Maja’s body move in tune with her breathing under the duvet. He was watching the light conquer the corners of the room when the ringing of the telephone broke the silence. He dragged himself over to the device and heard a raspy, elderly baritone from the other side. “Bašić speaking.”He didn’t immediately work out who he was talking to. He stood in the hallway, barefoot, telephone in hand, sifting through his memory, hoping to connect the name he’d just heard to a voice and a face. “Bašić, your former neighbour,” the man on the other side added, as if he’d realized what was going on. “Apologies for calling so early, but I think you should come over to Sts. Cyril and Methodius Street.” In that moment, Niko connected the voice coming from the receiver with a face which surfaced from the past. He knew who Bašić was. And he knew exactly what he was calling about.